Leukotriene B4 indicates lung injury and on-going inflammatory changes after severe trauma in a porcine long-term model. (December 2017) - Störmann, Philipp; Auner, Birgit; Schimunek, Lukas; Serve, Rafael; Horst, Klemens; Simon, Tim-P.; Pfeifer, Roman; Köhler, Kernt; Hildebrand, Frank; Wutzler, Sebastian; Pape, Hans-Christoph; Marzi, Ingo; et al.
Abstract: Background: Recognizing patients at risk for pulmonary complications (PC) is of high clinical relevance. Migration of polymorphonuclear leukocytes (PMN) to inflammatory sites plays an important role in PC, and is tightly regulated by specific chemokines including interleukin (IL)−8 and other mediators such as leukotriene (LT)B4. Previously, we have reported that LTB4 indicated early patients at risk for PC after trauma. Here, the relevance of LTB4 to indicating lung integrity in a newly established long-term porcine severe trauma model (polytrauma, PT) was explored. Methods: Twelve pigs (3 months old, 30 ± 5 kg) underwent PT including standardized femur fracture, lung contusion, liver laceration, hemorrhagic shock, subsequent resuscitation and surgical fracture fixation. Six animals served as controls (sham). After 72 h lung damage and inflammatory changes were assessed. LTB4 was determined in plasma before the experiment, immediately after trauma, and after 2, 4, 24 or 72 h. Bronchoalveolar lavage (BAL)-fluid was collected prior and after the experiment. Results: Lung injury, local gene expression of IL-8, IL-1β, IL-10, IL-18 and PMN-infiltration into lungs increased significantly in PT compared with sham. Systemic LTB4 increased markedly in both groups 4 h after trauma. Compared with declined plasma LTB4 levels in sham, LTB4 increased further in PT after 72 h. Similar increase was observed in BAL-fluid after PT. Conclusions: In a severe trauma model, sustained changes in terms of lung injury and inflammation are determined at day 3 post-trauma. Specifically, increased LTB4 in this porcine long-term model indicated a rapid inflammatory alteration both locally and systemically. The results support the concept of LTB4 as a biomarker for PC after severe trauma and lung contusion. Highlights: LTB4 rises locally and systemically with increasing lung injury after trauma in the porcine polytrauma model. Local inflammatory markers (IL-8 expression and PMN infiltration) are increased after trauma in the porcine polytrauma model. LTB4 is a potential biomarker to indicate lung injuries and on-going inflammatory changes after polytrauma not only in human patients but in the presented porcine polytrauma model as well.